Tributação Ambiental: a extrafiscalidade como instrumento estatal de preservação do meio ambiente - Badr, Fernanda Matos (2011)
The present study, considering the fact that nowadays we can not conceive the development process decoupled from the idea of environmental protection and preservation, investigates the principles, standards and administrative instruments and procedures of environmental law, that ensure the preservation of environment and the compensation for the damage caused. The Federal Constitution, in Article 225, caput, erected to the level of fundamental right the ecologically and balanced environment, essential to a healthy quality of life. This fundamental right to the environment is self-administered, indispensable, indivisible and inalienable, imposing upon the Government, together with society, duty, and not mere power, to defend it and preserve it for present and future generations. This study demonstrates that insofar as the Constitution and other rules that make the legal duty to the State, also give it the means to do it, in other words, the legal and financial resources it needs to meet expenses that will perform these tasks. So, at the same time that the responsibilities and duties are given to the State, are also given the power to tax. It can be said that the tax, primarily aims to raise funds, but can also be an instrument used by the State to interfere in the economic domain, in order to encourage or discourage certain practices or behaviors. This practice is known as extrafiscality and it can provide a variety of purposes, including the protection and defense of the environment, when, the tax is not only used to collect, but interfere on the economic agents will inhibiting environmentally undesirable choices or even encouraging other desirable under an environmental perspective. So, the stimulating functions or the extrafiscality can be considered as an instrument of state for environmental conservation, when the tax is used by the state to induce behaviors. At the end of this study, aiming to highlight what is considered abstractly, the last chapter studies the species capable of fulfilling such tax purposes and includes some examples that show the Brazilian normative materialization of that form of taxation. Thus, we conclude that our laws admit extrafiscality legally as skilled and effective disposal of the state for intervention in the economic domain with the purpose of environmental protection and preservation.